Ultrasonic-Assisted Extraction of Phytochemicals from Eggplant Peel: Physicochemical and Antibacterial Evaluation (Journal of Scientific Research, 2022)
The present study aimed to prepare and characterize eggplant peel extract (EPE) with suitability for application in the food industry. EPE was prepared via ultrasound-assisted extraction method employing ethanol as an extraction solvent, then reconstituted in water. The total phenolic content, anthocyanin content, and antioxidant activity of EPE in an organic and aqueous solvent were determined. In EPE, the major anthocyanin, delphinidin-3-rutinoside, was quantified via LC-MS/MS. The agar well diffusion assay and minimum inhibitory concentration (MIC) determination method were used to analyze the antibacterial activity of EPE against Bacillus cereus, Staphylococcus aureus, Escherichia coli, and Salmonella typhimurium. There was no significant difference (p>0.05) in the total phenolic content, anthocyanin content, and antioxidant activity of EPE when reconstituted in water. The inhibition zones of EPE (at 100 mg/mL concentration) ranged from 15.6 to 21.6 mm, whereas MIC ranged from 2.34 to 4.68 mg/mL against all tested bacteria. The lower values of MIC for B. cereus and S. aureus indicated that EPE was more effective for gram-positive bacterial strains. The water-reconstituted EPE with significant antioxidant and antibacterial activity would have potential food industrial applications, like food packaging, nutraceuticals, and functional foods.